IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR RAHMATAN LIL ALAMIN (PPRA) TERHADAP PEMAHAMAN PESERTA DIDIK TENTANG NILAI PENDIDIKAN ISLAM - Abdul Haris; Kholis; Siti Nurjanah (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
Globalization has had a significant impact on various aspects of social, cultural, and economic life. This process has brought rapid and widespread change, including in the education system. Islamic schools, as educational institutions oriented toward Islamic values, face new challenges and opportunities along with the penetration of global influences. Education based on the Rahmatan Lil Alamin Student Profile Strengthening Project (PPRA) is the right solution to strengthen understanding of Islamic educational values. This study aims to determine the concept of project-based learning to strengthen the profile of Rahmatan Lil Alamin Students, how it is implemented in madrasas and what impact it has on students' understanding of Islamic Education values ​​in class VII MTs. Al-Mu'min Tasikmalaya. This study uses a qualitative approach with a descriptive research type. The subjects of the study were the head of the madrasa, the vice curriculum and PPRA coordinator, teachers (PPRA Facilitators) and students. Data collection was carried out through observation, interviews, tests and documentation. The data analysis techniques used were data reduction, data presentation and drawing conclusions. The results of the study showed that: First, the PPRA concept integrated with the AkidahAkhlak subject at MTs. Al-Mu'min Tasikmalaya has been running very well, both in co-curricular and extracurricular activities. Although, PPRA is still implemented gradually, namely only for grade 7, while grades 8 and 9 are still implementing the 2013 Curriculum. Second, the implementation of PPRA is carried out in the form of co-curricular and extracurricular activities, with the themes of creative devotion, organic waste and the importance of democracy. Third, Impact In terms of cognitive, students show an increase in understanding of religious concepts that are deeper and more holistic. In terms of affective, PPRA increases student motivation and involvement in Islamic Religious Education learning and other learning. In terms of psychomotor, PPRA allows students to develop practical skills that are relevant to Islamic Religious Education subjects.